2021
DOI: 10.3389/fneur.2021.667651
|View full text |Cite
|
Sign up to set email alerts
|

Serum Homocysteine Level Is a Predictor of Relapse and Prognosis in Patients With First-Attack Neuromyelitis Optica Spectrum Disorders

Abstract: Background: Many patients with neuromyelitis optica spectrum disorders (NMOSD) experience the adverse consequences of relapse and disability aggravation. Thus, it is necessary to identify sensitive and reliable biomarkers for early prognosis. This study investigated whether serum homocysteine (Hcy) level was associated with the risk of relapse or poor prognosis in first-attack NMOSD patients.Methods: We enrolled 161 first-attack NMOSD patients in this retrospective study. We reviewed their medical records and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Elevated Hcy levels could cause oxidative stress, mitochondrial dysfunction, myelin sheath degeneration, and apoptosis ( 32 34 ). In our previous study, we found that Hcy was an independent predictor of relapse and poor prognosis in first-attack NMOSD patients ( 31 ). In the present study, we found that serum Hcy levels were higher in patients with EDSS >3 than in patients with EDSS ≤3 and positively correlated with the severity of neurological dysfunction at onset of MOGAD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Elevated Hcy levels could cause oxidative stress, mitochondrial dysfunction, myelin sheath degeneration, and apoptosis ( 32 34 ). In our previous study, we found that Hcy was an independent predictor of relapse and poor prognosis in first-attack NMOSD patients ( 31 ). In the present study, we found that serum Hcy levels were higher in patients with EDSS >3 than in patients with EDSS ≤3 and positively correlated with the severity of neurological dysfunction at onset of MOGAD.…”
Section: Discussionmentioning
confidence: 95%
“…Serum Hcy levels were found to be associated with the prognosis of MS and NMOSD ( 30 , 31 ). Elevated Hcy levels could cause oxidative stress, mitochondrial dysfunction, myelin sheath degeneration, and apoptosis ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first finding was that the Hcy level might be an independent risk factor for AQP4-IgG-positive highly active NMOSD. The second finding was that the Hcy level could predict relapse and prognosis in patients with first-attack NMOSD ( 40 ). In addition, another research team found that plasma Hcy levels were associated with EDSS in NMOSD ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Hcy will lead to neuronal damage, as the nervous system is particularly sensitive. Serum Hcy levels can also be used as an independent predictor of recurrence and poor prognosis for NMOSD patients [ 10 ]. For most patients with SCD or NMOSD, MRI results are always delayed behind the clinical presentation; therefore, long-term follow-up is needed.…”
Section: Discussionmentioning
confidence: 99%